Acute necrotizing enterocolitis due to sigmoid colon cancer: a rare entity case report - Sudiatmika, Dewa Gede; Trihatmaja, I. Gusti Ngurah A. Bayu; Ramayadnya, Anak Agung Gede Agung Wahyu; Jayaningrum, Gusti Ayu Agung Bella; Dinata, Gusti Ngurah Krisna; Adiputra, Pande Made Gunawan (International Journal of Research in Medical Sciences, 2021)
Adult necrotizing enterocolitis and non-occlusive mesenteric ischemia are rare causes of acute abdomen. Necrotising enterocolitis usually affects children and only few cases have been described in adults especially in geriatric patient. We report a rare case of acute necrotizing colitis of a 61 years old male patient. X-ray abdomen led to bowel dilatation. We performed emergency laparotomy under general anaesthesia and revealed that the dilatation of intestines and colon was caused by obstructive colitis due to sigmoid tumour. The digestive system was expanded proximally and the mucosae was seen turning black from the sigmoid colon to 80 cm proximal to the terminal ileum, from the findings we concluded that the patient was suffering from acute necrosis without significant vessel occlusion. The occlusion from the tumour may increase intraluminal pressure that affect colonic blood flow, and in closed-loop colonic obstruction without perforation, mucosal ischemia may be the primary event leading to massive colonic gangrene. Necrotising enterocolitis usually affects children and only few cases have been described in adults especially in geriatric patient. We performed complete colectomy with 90 cm resection of terminal ileum and ileostomy to remove the necrotic colon during surgery. Hartmann procedure was performed to distal part of rectum. The surgery was successful and patient was stable after the surgery.